Productive performance of soybean (Glycine max) using lactofen as a growth regulator - Campos de Almeida, Luiz Henrique; Sigari Lobato, Igor; Pinheiro Sanches de Almeida, Paula; Adolfo de Freitas Fregonezi, Gustavo (Revista de Ciências Agro-Ambientais, 2024)
The aim of this study was to evaluate the agronomic performance and productivity of soybean (Glycine max) using Lactofen as a growth regulator at different doses and phenological stages. The experiment was conducted at the Unifil School Farm in Londrina, Paraná, during the 2018/2019 growing season. The experimental design was a randomized complete block with five replications. The treatments consisted of three doses of the herbicide Lactofen: 0, 120, and 240 g L-1 a.i., and two phenological stages: V5 and V8. T1 controle 0 g L-1 i.a. de Lactofen, T2 240 g L-1 i.a. de Lactofen aplicado em V5, T3 240 g L-1 i.a. de Lactofen aplicado em V8, T4 120 g L-1 i.a. de Lactofen aplicado na V5 + 120 g L-1 i.a. de Lactofen aplicado em V8. Plots were 5.0 m long and 5.0 m wide, totaling 25.0 m2. Plant height, number of nodes, number of grains per pod, number of pods, weight of 1,000 grains, and yield in kg ha-1 were evaluated. Data were subjected to analysis of variance, and means were compared by Tukey’s test at 5% probability of error. The doses of Lactofen 0, 120, and 240 g L-1 a.i. had little impact on soybean’s productive components, showing no significant differences. The dose of 240 g L-1 a.i. applied at V8 resulted in higher productivity compared to the other treatments.